Ethical Leadership of Administrators that Affecting the Work Effectiveness of Schools Under the Sakon Nakhon Primary Educational Service Area Office 2 - Khi-in-thi, Prapaporn (Journal of Graduate MCU KhonKaen Campus, 2025)
This study aimed to: (1) examine the levels of ethical leadership of school administrators and school effectiveness under the Office of Sakon Nakhon Primary Educational Service Area 2; (2) investigate the relationship between administrators’ ethical leadership and school effectiveness; (3) analyze the predictive power of ethical leadership on school effectiveness; and (4) propose guidelines for developing administrators’ ethical leadership to enhance school effectiveness. The sample consisted of 391 administrators and teachers selected through multi-stage random sampling. The research instrument was a five-point rating scale questionnaire with validity ranging from 0.80–1.00, discrimination indices from 0.459–0.914, and reliability coefficients from 0.984–0.987. Data were analyzed using frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, and stepwise multiple regression. The findings revealed that: 1. both administrators’ ethical leadership and school effectiveness were rated at a high level 2. administrators’ ethical leadership was strongly and positively correlated with school effectiveness, with statistical significance at the .01 level 3. the aspects of respect, justice, and responsibility significantly predicted school effectiveness, jointly explaining 73.60% of the variance (R = .736, SE = .268) 4. eighteen feasible and appropriate guidelines were proposed for developing administrators’ ethical leadership in three key areas: respect, justice, and responsibility.